Plan de exportación de féretros colombianos a Nueva Zelanda (2021)
In this document we can find a compilation of literature that was use to build a methodology for the development of an export plan for Colombian coffins, produced by the company MACOFUN S.A.S to New Zealand, also we can find an analysis of the incident of this type of market within the economy for both countries, all the information was recognized and organized after a carried documentary review, that was useful to determine the economic and financial viability of the project, in order to generate a successful export strategy and achieve and increase of production in the funeral sector.